If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (7x + 2) * 3 + 8x = 0 Reorder the terms: (2 + 7x) * 3 + 8x = 0 Reorder the terms for easier multiplication: 3(2 + 7x) + 8x = 0 (2 * 3 + 7x * 3) + 8x = 0 (6 + 21x) + 8x = 0 Combine like terms: 21x + 8x = 29x 6 + 29x = 0 Solving 6 + 29x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 29x = 0 + -6 Combine like terms: 6 + -6 = 0 0 + 29x = 0 + -6 29x = 0 + -6 Combine like terms: 0 + -6 = -6 29x = -6 Divide each side by '29'. x = -0.2068965517 Simplifying x = -0.2068965517
| 2x^2+3x=81 | | 12+3(8+x)= | | 0.03=3.5c-1.02 | | 0.3=-6 | | 9+5(4x+4)= | | 5z+58=14z+4 | | 3m^2=3-8m | | 1.32+1.5=5.4 | | 3m^2=3-8 | | 7(2+3x)+8= | | 0.6x=-9 | | 8x+4x+5x=7 | | p+-2=21 | | 18z+3=9z+48 | | 0.5(-4+6x)=0.3x+0.67(x+9) | | 36x^2-225=0 | | ln(x+9)+ln(x-4)=2ln(x) | | -3x^2+42x-147=0 | | x^2-40=3x | | m^2+2m+6=0 | | 100x^2=49 | | 25x+10x+7=0 | | 2x^2+5=31 | | -4-11+17*4=53 | | 15z-4=7z+36 | | x-19.7=-17.48 | | 0=x^2-x-12 | | 90y+36-72y=30 | | y=2x^3-3x^2-36x+9 | | y=4-2*-3 | | 0.5a+9=2a-6 | | 553+47+30+68+35+45= |